The Perception of MTsN 8 Agam Students on Teaching Competence of Student Teacher from PAI Department of STAI-PIQ West Sumatera 2019-2020 - Hasnah Hasnah; Martono Martono (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2020)
Practical Field Experience (PPL) aims to shape students into prospective professional educational staff. PPL is also a special course for Islamic Religious Education (PAI) study program students who are given in semester VIII to apply the theories they have acquired during lectures and are part of the curriculum that has become a stipulation for Sekolah Tinggi Agama Islam Pengembangan Ilmu Alquran (STAI-PIQ), especially in this study are students of the Islamic Religious Education Study Program at semester VIII of the 2019/2020 Academic Year. The population in this study were students of MTsN 8 Agam Bukittinggi in class VII as many as five locales consisting of VII-1, VII-2, VII-3, VII-4, VII-5, totaling 126 students, taken as many as 95 samples. , the sample is taken randomly. The method used is a quantitative method with percentage descriptive analysis. The conclusion of this study is that the perceptions of MTsN 8 Agam students towards the teaching competence of PPL students of the PAI STAI-PIQ West Sumatra Study Program in 2019/2020 are categorized as good with four competencies, namely pedagogic competence, personal competence, social competence, and professional competence. One of the four competencies, namely personality competence, is in the very good category. Even so, there are still many competency indicators that have not been mastered by PPL students of PAI STA-PIQ West Sumatra Study Program. Praktek Pengalaman Lapangan bertujuan membentuk mahasiswa menjadi calon tenaga kependidikan yang professional. PPL juga merupakan mata kuliah khusus bagi mahasiswa prodi PAI yang diberikan pada semester VIII untuk mengaplikasikan teori yang telah mereka peroleh selama perkuliahan dan merupakan bagian kurikulum yang sudah menjadi ketetapan bagi STAI-PIQ, yang khususnya dalam penelitian ini adalah mahasiswa Program Studi Pendidikan Agama Islam di semester VIII Tahun Ajaran 2019/2020. Populasi dalam penelitian ini adalah peserta didik MTsN 8 Agam Bukittinggi di kelas VII sebanyak lima local yang terdiri dari VII-1, VII-2, VII-3, VII-4, VII-5 yang berjumlah 126 peserta didik, diambil sampel sebanyak 95 orang, sampel diambil secara random. Metode yang dipakai adalah metode kuantitatif dengan analisis secara deskriptif persentase. Kesimpulan penelitian ini adalah, bahwa persepsi peserta didik MTsN 8 Agam terhadap kompetensi mengajar mahasiswa PPL Prodi PAI STAI-PIQ Sumatera Barat tahun 2019/2020 termasuk dalam ketegori baik dengan empat kompetensi yaitu kompetensi pedagogic, kompetensi kepribadian, kompetensi social, dan kompetensi professional. Satu diantara empat kompetensi yaitu kompetensi kepribadian masuk kategori baik sekali. Meskipun demikian masih banyak indikator-indikator kompetensi yang belum dikuasai mahasiswa PPL Prodi PAI STA-PIQ Sumatera Barat.